(untitled) (The Peerian Journal, 2024)
The aim of this study was to analyze the effectiveness of kinesiotherapy in the rehabilitation of children with recurrent obstructive bronchitis (ROB) who had COVID-19 by determining spirometric indicators. The subjects were children aged 7 to 15 years with recurrent obstructive bronchitis, and the initial indicators of their external respiratory function (FER) were determined during the exacerbation period. In the experimental group, rehabilitation measures included the effective integration of kinesiotherapy (KT). A comparative study of the respiratory function in children with recurrent obstructive bronchitis after a six-month course of kinesiotherapy demonstrated the positive effectiveness of the method: an increase in the number of children with standard values of VC from 76.4% to 98.7%, FVC from 51.4% to 82.3%, FEV1 from 52.3% to 93.1%, IT from 64.5% to 89%, POS from 61.2% to 94.1%, MOS-75 from 65.9% to 92.2%, and MVL on average from 27.2 L to 46.3 L was observed. In children with ROB, there was a decrease in the number of hospitalizations, the frequency of recurrent bronchial obstruction, and the duration of exacerbations; doses of medications were reduced or discontinued during the recovery period. The results showed that the use of kinesiotherapy in patients with ROB increases the functional capabilities of the respiratory system and has a positive effect on rehabilitation